Anthropogenic climate change in an integrated energy balance model of global and urban warming - Kimitoshi Sato (Journal of Economic Structures, 2014)
This paper presents an integrated energy balance model of global and urban warming in the attributes/functionings framework à la Gorman-Lancaster-Sen and proposes a Global Warming Function and an Urban Warming Function. Also presented is a concept of Heat Island Integral, which measures the difference of anthropogenic heat stocks between two regions. The model involves residents, producers such as offices and manufacturers, and landscape gardeners who play a very important role in cooling down by roof-top gardening and tree-planting activities, etc. It is shown that urban warming tax/subsidy scheme is designed as a Groves mechanism by the implementation theory.
Keywords: H2; Q24; R13; R14; 330; Anthropogenic heat stocks; Attributes/characteristics à la Gorman-Lancaster; Biological attributes; Global warming function; Heat island integral; Landscape gardener; Microclimate; Sen's functionings; Urban warming function; Urban warming tax/subsidy scheme